Identification of a conserved family of Meis1-related homeobox genes. - Steelman, S; Moskow, J J; Muzynski, K; North, C; Druck, T; Montgomery, J C; Huebner, K; Daar, I O; Buchberg, A M (Genome Research, 1997)
Meis1 locus was isolated as a common site of viral integration involved in myeloid leukemia in BXH-2 mice. Meis1 encodes a novel homeobox protein belonging to the TALE (three amino acid loop extension) family of homeodomain-containing proteins. The homeodomain of Meis1 is the only known motif within the entire 390-amino-acid protein. Southern blot analyses using the Meis1 homeodomain as a probe revealed the existence family of Meis1-related genes (Mrgs) in several diverged species. In addition, the 3' untranslated region (UTR) Meis1 was remarkably conserved in evolution. To gain a further understanding of the role Meis1 plays in leukemia and development, as well as to identify conserved regions of the protein that might reveal function, we cloned and characterized Mrgs from the mouse and human genomes. We report the sequence of Mrg1 and MRG2 as well as their chromosomal locations in murine and human genomes. Both Mrgs share a high degree of sequence identity with the protein coding region of Meis1. We have also cloned the Xenopus laevis ortholog of (XMeis1). Sequence comparison of the murine and Xenopus clones reveals that Meis1 is highly conserved throughout its coding sequence as well as the 3' UTR. Finally, comparison of Meis1 and the closely related Mrgs to known homeoproteins suggests that Meis1 represents a new subfamily of TALE homeobox genes.